Activated Natural Killer Cell Promotes Nonalcoholic Steatohepatitis Through Mediating JAK/STAT PathwaySummary - Feixue Wang (Elsevier, 2022)
Background & Aims: Hepatic immune microenvironment plays a pivotal role in the development of nonalcoholic steatohepatitis (NASH). However, the role of natural killer (NK) cells, accounting for 10%–20% of liver lymphocytes, in NASH is still unclear. In this study, we aim to investigate the functional significance of NK cells in NASH evolution. Methods: NASH was induced in mice fed methionine- and choline-deficient diet (MCD), choline-deficient high-fat diet (CD-HFD), or high-fat diet with streptozotocin injection (STAM model). NK cell deficient mice (Nfil3-/-) and neutralization antibody (PK136) were used in this study. Results: Activated liver NK cells were identified with increased expression of NKG2D, CD107a, and interferon-γ but decreased inhibitory NKG2A. With NK cell deficiency Nfil3-/- mice, the absence of NK cells ameliorated both MCD- and CDHF- induced NASH development with significantly decreased hepatic triglycerides, peroxides, alanine aminotransferase, and aspartate aminotransferase compared with Nfil3+/+ mice. Further molecular analysis unveiled suppressed pro-inflammatory cytokines and associated signaling. Mechanistically, NK cells isolated from NASH liver secreted higher levels of pro-inflammatory cytokines (interferon-γ, interleukin 1β, interleukin 12, CCL4, CCL5, and granulocyte-macrophage colony-stimulating factor), which could activate hepatic JAK-STAT1/3 and nuclear factor kappa B signaling and induce hepatocyte damage evidenced by elevated reactive oxygen species and apoptosis rate. Moreover, neutralization antibody PK136-dependent NK cell depletion can significantly alleviate MCD-induced steatohepatitis with suppressed cytokine levels and JAK-STAT1/3 activity. Conclusions: NK cells in NASH liver are activated with a more pro-inflammatory cytokine milieu and promote NASH development via cytokine-JAK-STAT1/3 axis. Modulation of NK cells provides a potential therapeutic strategy for NASH.